Imaging of osteo-odonto-keratoprosthesis by electron beam tomography. Issue 8 (15th July 2005) - Fong, K C S; Ferrett, C G; Tandon, R; Paul, B; Herold, J; Liu, C S C
Abstract : Aim: To describe the experience of using electron beam tomography (EBT) in imaging of osteo-odonto-keratoprosthesis (OOKP) to identify early bone and dentine loss which may threaten the viability of the eye. Methods: Seven patients with an OOKP in one eye underwent EBT. The OOKP lamina dimensions were measured on EBT and compared to the manual measurements at the time of surgery. Results: There was a high degree of resolution of the OOKP lamina noted with EBT. In particular, it identified three patients with a marked degree of thinning of the lamina edges. Two of these patients had OOKP that were allografts. The mean time from surgery to examination was 3.6 years (range 1.2–5 years) while the mean age of the patients was 56 years (range 31–79 years). Conclusions: It is important to monitor regularly the dimensions and stability of the OOKP lamina as it will help detect cases that are at risk of extrusion of the optical cylinder and consequent endophthalmitis. Prophylactic measures can then be taken to prevent such serious complications from occurring. In this series, the authors found EBT to have excellent resolution and speed and they would support regular scanning of the OOKP lamina in all patients.